1993
DOI: 10.1021/bi00074a011
|View full text |Cite
|
Sign up to set email alerts
|

Selective action of 4'-azidothymidine triphosphate on reverse transcriptase of human immunodeficiency virus type 1 and human DNA polymerases .alpha. and .beta.

Abstract: 4'-Azidothymidine (ADRT) is a novel nucleoside analogue that exhibits potent inhibitory activity against the replication of human immunodeficiency virus (HIV) in lymphocytes. The mechanisms by which ADRT inhibits HIV reverse transcriptase (HIV-RT) as ADRT 5'-triphosphate (ADRT-TP), the active intracellular metabolite of ADRT, and as the ADRT-MP molecule incorporated into DNA were examined and compared to their effects on human DNA polymerases alpha and beta. Inhibition of HIV-RT by ADRT-TP is competitive again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Additionally, nucleoside analogs substituted at the 4Ј-position have also been described previously (43)(44)(45)(46). For example, 4Ј-azidothymidine and 4Ј-azidoadenosine both inhibit HIV-1 replication (46) although with potencies 200 -2000-fold less than that of EFdA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, nucleoside analogs substituted at the 4Ј-position have also been described previously (43)(44)(45)(46). For example, 4Ј-azidothymidine and 4Ј-azidoadenosine both inhibit HIV-1 replication (46) although with potencies 200 -2000-fold less than that of EFdA.…”
Section: Discussionmentioning
confidence: 99%
“…Both 4Ј-azido nucleosides also have poor in vitro selectivity indices because of significant cytotoxicity. Azidothymidine-TP was shown to inhibit RT-catalyzed DNA synthesis by a type of delayed chain termination; incorporation of two sequential azidothymidine-MP molecules blocked DNA synthesis (44,45). 4Ј-Methyl thymidine and 4Ј-ethyl thymidine both seem to cause pauses and stops in DNA synthesis at the point of incorporation (39).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the mechanism of antiviral activity of EFdA, previous reports of 4Ј-substituted-2Ј-deoxynucleosides, such as 4Ј-AZT, have shown that following intracellular anabolism to the 5Ј triphosphate, HIV-1 reverse transcriptase (RT) efficiently incorporated the nucleotide, which prevented further chain elongation of the viral DNA (4,5). Although the rate of incorporation for the 5Ј-triphosphate of 4Ј-AZT was quite low, HIV-1 RT was able to incorporate two consecutive molecules efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…For elution, the following program was used: 5 min of buffer A, followed by 10 min of a highly convex gradient to 75% buffer A-25% buffer B, followed by 15 min of a slightly convex gradient to 100% buffer B, and finally followed by a 10-min isocratic elution with buffer B. One-minute elution fractions were collected, and the radioactivity of each fraction was measured using a liquid scintillation counter to determine the amount of metabolites. (2,4,8,12, and 24 h). The amounts of intracellular metabolites were determined by HPLC analysis as described above.…”
Section: Methodsmentioning
confidence: 98%
“…While we were working on our project, the anti-HIV activity of several 4'SdNs was reported by the Syntex group [16][17][18][19][20][21][22] and others [23,24]. Therefore, the anti-HIV activities of 4'SdNs that we studied together with those reported by other groups are listed in Table 2.…”
Section: Structure-activity Relationship (Sar) Of 4'sdnsmentioning
confidence: 87%